Vibration Attenuation of Plate using Multiple Vibration Absorbers - M. S. M., Sani; Izzuddin, Zaman; Muhammad, Mohamed Salleh; Maznan, Ismon; Bukhari, Manshoor; Amir, Khalid; Sherif, Araby (2014)
Vibrations are undesired phenomenon and it can cause harm, distress and unsettling influence to the systems or structures, for example, aircraft, automobile, machinery and building. One of the approach to limit this vibration by introducing passive vibration absorber attached to the structure. In this paper, the adequacy of utilizing passive vibration absorbers are investigated. The vibration absorber system is designed to minimize the vibration of a thin plate fixed along edges. The plate's vibration characteristics, such as, natural frequency and mode shape are determined using three techniques: theoretical equations, finite element (FE) analysis and experiment. The results demonstrate that the first four natural frequencies of fixed-fixed ends plate are 48, 121, 193 and 242 Hz, and these results are corroborated well with theoretical, FE simulation and experiment. The experiment work is further carried out with attached single and multiple vibration absorbers onto plate by tuning the absorber's frequency to match with the excitation frequency. The outcomes depict that multiple vibration absorbers are more viable in lessening the global structural vibration.